(3GdehGLgI GdLfGFjI ddGYeGd GdGQgGHjI (B:s (3OQGSI ebGQfI (B/s - (3MSjf eMeO MSjf GdHhYdis; (3GMeO YhV HdGds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2022)
(3de jbJUQ GdEQgGH Ydi HK GdQYH, hGdNha, hGdVZW Ydi GdMcheGJ, hEcQGggG Ydi JfajP CZQGVgG GdELQGejI, hEfeG CNP HGdJbfjGJ GdMOjKI, aXgQ Ydi GdSGMI eG jSei HGdEQgGH GdEdcJQhfj, hGdCSdMI GdaJGcI GdJbdjOjI, hZjQ GdJbdjOjI; dJfajP eBQHg, ade nqJoYO GdCSdMI GdJbdjOjI PQGYg GdWhdj, hEfeG UGQJ GdLeGYGJ GdEQgGHjI JCNP HGdhSGFd GdMOjKI, hGSJZdGd GdehGbY GdEdcJQhfjI, hJSNjQgG dJMbjb CgOGagG ef NdGd GdJQhjL dCacGQ GdefXeGJ GdEQgGHjI, Ch GdOYhi Edi GdGfVeGe EdjgG, Ch GdJNWjW dJfajP LQGFegG, hjJe Jehjd gPG GdEQgGH ef Ohd HPGJgG JQYGg, hJfXjeGJ OhdjI JDGRQg, hJToqO ef CRQg, HGdSdGM hGdeGd, hGdOYe GdeYfhj(B. (3hbO COi GdZehV GdPj jcJfa GdEQgGH Edi JSGQY cGaI GdOhd Edi Sf GdJTQjYGJ; dehGcHI gPg GdXGgQI GdELQGejI GdHGdZI GdNWhQI, hGdMO ef JhZdgG hGfJTGQgG, MQkUG Ydi GdCef Gdbhej hMbhb GdEfSGf aj EWGQ ef GdehGRfI Hjf GSJbQGQ GdfXGe GdYGe, hGMJQGe Mbhb GdEfSGf hMQjGJg GdCSGSjI, aj efXheI hGMOI JSjQ LfkHG Edi LfH(B.s
Terrorism was not limited to spreading terror and fear, putting pressure on governments, and coercing them to carry out their criminal purposes, but rather it adopted modern technologies. The so-called electronic terrorism and conventional and non-traditional lethal weapons appeared on the scene. To carry out his goals, conventional weapons are no longer his longitudinal arm, but terrorist groups are adopting modern means, exploiting websites, and harnessing them to achieve their goals by promoting the ideas of terrorist organizations, or calling for joining them, or planning to carry out their crimes, and this terrorism is financed by countries themselves. It sponsors him, and international organizations support him and strengthen him, with weapons, money, and moral support. The ambiguity surrounding terrorism has prompted all countries to enact legislation; To keep pace with this extremely dangerous criminal phenomenon, and to limit its penetration and spread, in the interest of national security and human rights within a framework of balancing the stability of public order, and respect for human rights and fundamental freedoms, in one system that goes hand in hand.
(3CWQhMI (B((3OcJhGQg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdLfGFj, (B2022s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B482-527s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdehGLgI GdLfGFjIs; (3GdGYeGd GdGQgGHjIs; (3Gef GdOhdI GdOGNdjs; (3Gef GdOhdI GdNGQLjs; (3MeGjI GdfXGe GdYGes; (3GdXQha GdeTOOI s; (3GdYbhHGJ GdebQQI Ydj GdLQGFe GdGQgGHjIs; (3GdXQha GdeNaaIs; (3GdMHS GdGMJjGWjs; (3GYJQGV GJUGdGJ GdeJges; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs